2017
DOI: 10.1039/c7ob02303k
|View full text |Cite
|
Sign up to set email alerts
|

Decoding glycan protein interactions by a new class of asymmetric N-glycans

Abstract: N -glycans are normally involved in crucial physiological and disease processes by interactions with glycan binding proteins. So far structurally defined N-glycans are good candidates for glycan binding study. Herein, a class of homogeneous asymmetric N-glycans was synthesized by coupling glycan-oxazoline and N-glycans using EndoM N175Q catalyzed quick glycan extension. Branch-biased binding and spacial inhibition caused by bulky group on the other branch of N-glycan were observed in glycan protein interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Bead-based arrays may be particularly useful for rapid customization (39). In addition, new synthetic methods are enabling the production of structures that were previously difficult to synthesize, such as asymmetrically branched N-glycans (40, 41), which could reveal unusual fine specificities in lectins or glycosidases (16). Integrating glycan-array analyses with lectin structural information (42) also promises to increase precision in charactering specificities.…”
Section: Discussionmentioning
confidence: 99%
“…Bead-based arrays may be particularly useful for rapid customization (39). In addition, new synthetic methods are enabling the production of structures that were previously difficult to synthesize, such as asymmetrically branched N-glycans (40, 41), which could reveal unusual fine specificities in lectins or glycosidases (16). Integrating glycan-array analyses with lectin structural information (42) also promises to increase precision in charactering specificities.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, new synthesis strategies have resulted in the production of an increasing diversity of higher-complexity structures. The new structures include various types of sialylated structures, human milk oligosaccharides, and asymmetrically branched N -glycans. , In addition, microarrays have been developed to cover additional classes of glycans, including arrays of microbial glycans, plant cell–wall glycans, and fully-defined heparan sulfate glycans . New experimental systems for glycan presentation and detection include a glycan bead array, a next-generation glycan microarray (NGGM), and a competitive universal proxy receptor assay (CUPRA) .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, recent advances in the preparation of the whole structure of various N -glycans have allowed the full realization of structure–activity relationships, elucidating the significance of complexity of N -glycan structures ( Figure 4 ). For example, these advances have provided insights into the differences in the lectin recognition of each branch [ 49 , 50 , 51 , 52 , 53 , 54 ], the improvement of affinity due to the inclusion of multiple recognition units (multivalent effect) [ 20 , 21 , 55 , 56 , 57 , 58 , 59 ], the influence of chain length on affinity [ 60 , 61 ], and remote (heterovalent) recognition [ 59 ].…”
Section: Elucidation Of the Molecular Basis Of N mentioning
confidence: 99%
“…Wang et al demonstrated the differences of each N -glycan branch in lectin recognition by comprehensive interaction analysis of various N -glycans with several lectins using a glycan array [ 53 , 54 ]. Plant-derived Sambucus nigra lectin (SNA), which recognizes sialic acid, recognized the sialic acid on the α1,3-branched chain more strongly than the sialic acid on the α1,6-branched chain.…”
Section: Elucidation Of the Molecular Basis Of N mentioning
confidence: 99%